2018
DOI: 10.3892/ol.2018.7866
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of isodicentric Ph chromosomes and the three-way Ph chromosome variant t(3;9;22)(p21;q34;q11) in a rare case of chronic myeloid leukemia

Abstract: Abstract. More than 90% of patients with chronic myeloid leukemia (CML) have the chromosomal translocation t(9;22)(q34;q11), while 5-8% of patients have complex variant translocations that have previously been thought not to affect the efficacy of imatinib therapy. The present study reports a patient with CML in B-lymphoid blast crisis who had a rare three-way Philadelphia (Ph) variant t(3;9;22)(p21;q34;q11), in addition to isodicentric Ph chromosomes. The patient was initially treated with imatinib for >2 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Structural abnormalities involving the long arm of chromosome 3, e.g., t(3;9;22)(q21;q34;q11.2), have been associated with poor prognosis and decreased survival [6]. The 3q21 chromosome region harbors tumor suppressor genes H37, Luca15, RBM5, and RASSFIA, and tumor susceptibility genes like the hMLH1 [8].…”
Section: Philadelphia Chromosome Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural abnormalities involving the long arm of chromosome 3, e.g., t(3;9;22)(q21;q34;q11.2), have been associated with poor prognosis and decreased survival [6]. The 3q21 chromosome region harbors tumor suppressor genes H37, Luca15, RBM5, and RASSFIA, and tumor susceptibility genes like the hMLH1 [8].…”
Section: Philadelphia Chromosome Variantsmentioning
confidence: 99%
“…Some authors have suggested that these variants can arise through two mechanisms: the first, whereby three chromosomes simultaneously break, and the second, in which another chromosome attaches to a standard t (9;22) as a product of a clonal evolution. This second scenario is related to a poor prognosis [7,8]. Similarly, additional chromosomal alterations (ACAs) occur in approximately 5 % of CML cases.…”
Section: Introductionmentioning
confidence: 99%